China and the News of the Funan Techo Canal Project in Cambodia - Daris Abdul Aziz; Taufik Taufik (Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan, 2026)
The Funan Techo Canal is a strategic infrastructure project in Cambodia, part of the Belt and Road Initiative (BRI). The project aims to improve connectivity, strengthen economic autonomy, and reduce Cambodia's dependence on neighbouring countries. While widely supported for its potential to expand market access, create jobs, and boost economic growth, the project has also drawn criticism regarding its geopolitical, environmental, and security impacts in Southeast Asia. This study aims to analyse the development of the Funan Techo Canal project, the Cambodian public's response to its construction, and China's strategy for gaining public support through public diplomacy using the media. The study employed a qualitative method with a descriptive-analytical approach. Data were obtained through a literature review that included scientific journals, research reports, official documents, and Chinese media coverage. The analysis used a media approach and media framing to examine how public opinion was constructed. The results show that the project was promoted as a means of increasing economic growth, enhancing logistical independence, and developing national infrastructure. The Cambodian public's response tended to be positive because the project was perceived as capable of improving economic well-being. Through public diplomacy and strategy, Chinese media emphasised the development benefits and framed the project as a symbol of mutually beneficial cooperation. This strategy contributes to building a positive image of China and strengthening the legitimacy of the Funan Techo Canal project in the eyes of the Cambodian people and the international public.